2019
DOI: 10.1021/acs.chemmater.9b03740
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Flexibility of Mg in Pnictide Materials: Structure and Properties Diversity

Abstract: Magnesium, element no. 12 on the periodic table, is the second member of the alkaline-earth metal family. Often, Mg is considered as an electropositive metal like its heavier congeners, Ca, Sr, and Ba. In this review, another important aspect of Mg chemistry, namely, the ability to form covalent bonds to more electronegative elements, is considered with a focus on pnictides. Magnesium's flexible coordination numbers and bond distances are similar to those of main group elements (Al) or late-and post-transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 178 publications
0
15
0
Order By: Relevance
“…11 However, this picture is not suitable in the case of Mg 3 Sb 2 and Mg 3 Bi 2 ; in these binary compounds, Mg resides in both the octahedrally coordinated Mg1 site (i.e., the cation site) and the tetrahedrally coordinated Mg2 site (typically occupied by a more electronegative post-transition metal). 12 First-principles chemical bonding analysis has suggested that the Mg1−Sb and Mg2−Sb bonds in Mg 3 Sb 2 are quite similar with respect to the degree of charge transfer from Mg to Sb. 13 This prediction of quasi-isotropic bonding in Mg 3 Sb 2 was accompanied by first-principles calculations of nearly isotropic compressibility in the in-plane (a−b plane) and out-of-plane (c-axis) directions under pressure.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 However, this picture is not suitable in the case of Mg 3 Sb 2 and Mg 3 Bi 2 ; in these binary compounds, Mg resides in both the octahedrally coordinated Mg1 site (i.e., the cation site) and the tetrahedrally coordinated Mg2 site (typically occupied by a more electronegative post-transition metal). 12 First-principles chemical bonding analysis has suggested that the Mg1−Sb and Mg2−Sb bonds in Mg 3 Sb 2 are quite similar with respect to the degree of charge transfer from Mg to Sb. 13 This prediction of quasi-isotropic bonding in Mg 3 Sb 2 was accompanied by first-principles calculations of nearly isotropic compressibility in the in-plane (a−b plane) and out-of-plane (c-axis) directions under pressure.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the past five years, however, alloys between Mg 3 Sb 2 and Mg 3 Bi 2 have emerged as exceptional room-temperature thermoelectric materials, threatening to overthrow the decades-long reign of Bi 2 Te 3 . Mg 3 Sb 2 and Mg 3 Bi 2 are binary members of the CaAl 2 Si 2 structure type ( P 3̅ m 1) shown in Figure a, making them part of a broader family of AM 2 X 2 Zintl compounds that are traditionally considered to be layered materials. Many compounds in this family are well-described as consisting of covalent [M 2 X 2 ] 2– slabs with the ionically bonded interlayer A 2+ cations providing charge neutrality . However, this picture is not suitable in the case of Mg 3 Sb 2 and Mg 3 Bi 2 ; in these binary compounds, Mg resides in both the octahedrally coordinated Mg1 site (i.e., the cation site) and the tetrahedrally coordinated Mg2 site (typically occupied by a more electronegative post-transition metal) . First-principles chemical bonding analysis has suggested that the Mg1–Sb and Mg2–Sb bonds in Mg 3 Sb 2 are quite similar with respect to the degree of charge transfer from Mg to Sb .…”
Section: Introductionmentioning
confidence: 99%
“…This high abundance of NCS structures in a single system is not observed in binary metal pnictides or silicides, where the amount of NCS compounds is less than 10%. However, silicide-pnictides of alkaline-earth metals exhibit similar high abundance of NCS structures such as Mg-Si-As (2 out of 3 are NCS) 22,30 and Ba-Si-P (3 out of 5 are NCS). 8,9,19,20,31,32 We hypothesize that the ability of Si-P and Si-As substructures to provide flexible coordination environments to electropositive metals, due to multiple binding modes and localized electron lone-pairs on pnictogen atoms, is crucial for generation of such NCS structures in metal-tetrel-pnictide systems.…”
Section: Resultsmentioning
confidence: 99%
“…The Mg-Si-As ternary system has been overlooked for many years with only one theoretically predicted compound MgSiAs 2 (Woo et al, 2018). Our synthetic efforts discovered three new ternary compounds, MgSiAs 2 , Mg 3 Si 6 As 8 , and Mg 3 Si 3 As 8 (Woo et al, 2018;Wang et al, 2019). MgSiAs 2 was confirmed to have chalcopyrite structure type, while the other two compounds crystallize in new structure types.…”
Section: Bacu 2 P 4 In Sn Fluxmentioning
confidence: 91%